Flexible, Self-Determined… and Unhealthy? An Empirical Study on Somatic Health Among Crowdworkers - Schlicher, Katharina D.; Schulte, Julian; Reimann, Mareike; Maier, Günter W. (Frontiers in Psychology, 2021)
Crowdwork is a new form of digitally enabled work in which organizations assign tasks to an anonymous group of workers via platform intermediaries. For crowdworkers, crowdwork offers both opportunities and risks. On the one side, crowdworkers enjoy high flexibility on when, where, and how much to work. On the other side, risks comparable to other forms of atypical employment arise: no labor regulation, unstable income, and uncertainty about whether enough tasks are available. Regulation of working hours lies within the crowdworkers’ own authority. Also, crowdwork in industrialized nations is often conducted during leisure times as a side-job to some other kind of employment. In accordance with Conservation of Resources Theory, we state that when leisure time gets used up with crowdwork, regeneration cannot occur and health declines. On a sample of N = 748 German crowdworkers recruited from four different platform types, we analyzed whether participation in crowdwork is linked to increased somatic symptoms compared to regularly employed personnel. We found that crowdworkers show significantly increased somatic symptoms as compared to a German norm sample, that are stable across different kinds of tasks and platforms, gender, and age groups, and that is statistically due to the extent of participation in crowdwork. Specifically, we found that total work hours per week were not associated with an increase in somatic symptoms, but we did find associations with strain-based work-family conflict and the primary motivation to do crowdwork being to earn money. Consequences for research and labor regulations are discussed.